Reversible cerebral vasoconstriction syndrome shows different clinical pictures at different times during the perinatal period: Two case reports - Sena Hamano; Kaori Toda; Mayu Sato; Hiroko Taniguchi; Takatsugu Maeda; Katsufumi Otsuki; Masato Kamitomo; Yoshio Matsuda (Elsevier, 2024)
Objective: With the development of diagnostic imaging, a new clinical entity called reversible cerebral vasoconstriction syndrome (RCVS), which is considered to be a cause of secondary headache, has emerged. We herein present two cases of RCVS with different patterns of clinical progression. Case report: Case 1 occurred during labor, whereas case 2 occurred after delivery. Neither case presnted thunderclap headache at the onset of symptoms. Hypertensive disorders of pregnancy did not occur during the pregnancy or the puerperium in either case. Neurological symptoms following mild headache (Case 1: coma; Case 2: paralysis of the right extremities) were observed. Conclusion: Even when a patient has no risk factors for RCVS and had no severe headache, it is important not to miss any of the neurological symptoms. Magnetic resonance imaging (MRI) strongly supports the diagnosis, even during pregnancy. In addition, the diagnosis should always be reviewed while excluding eclampsia.